La primera tesis doctoral sobre feminismo: Jessie Taft sobre el movimiento de las mujeres desde el punto de vista de la conciencia social. - Miras Boronat, Núria Sara (Revista Estudios de Filosofía)
The dissertation The Woman Movement from the Point of View of Social Consciousness by Jessie Taft —written in 1913, published in 1915— "is perhaps the first doctoral thesis written on a feminist topic" (Seigfried, 1996, p. 46). However, this text has received little attention in the genealogies of both feminism and pragmatism. This article aims to defend the originality of Taft’s approach and the historical value of her thesis as an example of the ideological debates within the feminist movement. A biographical, historical, and literary contextualization of the thesis will be provided, followed by an assessment of her methodological decisions and argumentative strategies. This analysis will highlight the many gaps in the philosophical-political interpretation of the thesis, which can now only be filled speculatively, in the hope that more comprehensive and detailed future research will shed further light on the matter.